The Influence of E-Service Quality and Sales Promotion on Customer Satisfaction Mediated by Purchase Decisions and Their Impact on Customer Loyalty - Nabila Putri Deswara; AMA Suyanto (Lafadz Jaya Publisher, 2023)
The purpose of this research is to find out how consumer satisfaction can increase consumer loyalty, which is influenced by the quality of electronic services and the decision to make a purchase after seeing the sales promotion given. Data collection was carried out by distributing surveys via Google forms to 300 respondents who had used GoFood. Data is processed using SMART-PLS 3.2.9. The sample selection used a non-probability sampling technique, namely purposive sampling. The analysis technique used is SEM. The results of the study show consumer satisfaction can increase loyalty after satisfaction is influenced by the quality of electronic services received by consumers and purchase decisions that have been made after seeing the sales promotions given.